An Act to Prevent Popery within this Province, Votes and Proceedings of the Lower House of Assembly of the Province of Maryland (22 May, 1756). - (:unkn) unknown (General Publisher, 1756)
And be it further Enacted, That all such Armour, Gunpowder, and Ammunition, of whatsoever Kinds, as any Papist whatever, within this Province, hath or shall have in his House or Houses, or elsewhere, or in the Hands and Possession of any other Person at his or their Disposition, shall be taken from such Papist, or Others, which have or shall have the same to the Use of such Papist, by Warrant of any Four Justices of the Peace of the County where such Papist shall be Resident (other than such necessary Weapons as shall be thought fit by the same Justices to remain and be allowed for the Defence of the Person or Persons of such Papists, or for the Defence of his, her or their Houses
Keywords: GUN POWDER